Polymer fiber bragg gratings - Webb, David J.; Kalli, Kyriacos (My University, 2011)
This chapter deals with gratings recorded in polymeric optical fibers (POFs), predominantly those based on poly (methyl methacrylate) (PMMA). We summarize the different mechanical and optical properties of POFs which are relevant to the application of POF Bragg gratings and discuss the existing literature on the subject of the UV photosensitivity of PMMA. The current state of the art in POF grating inscription is presented and we survey some of the emerging applications for these devices.
Keywords: Polymeric optical fibers; Methyl methacrylate; UV photosensitivity